VD_FINDINFO HC / 2013 / 172 vom 6. März 2013 - VD Tribunal cantonal (2013)
EXPULSION DE LOCATAIRE, DEMEURE DU DÉBITEUR, LOYER, BAIL À LOYER, RÉSILIATION IMMÉDIATE, LOGEMENT | 257d CO, 7 al. 2 RULV, 308 al. 2 CPC (CH), 312 al. 1 CPC (CH), 317 CPC (CH)